Insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) in hematological diseases - Shuangping Ma; Yiran Qin; Wenjie Ren (BMC, 2024)
Abstract The oncofetal mRNA-binding protein IGF2BP1 belongs to a conserved family of RNA-binding proteins. It primarily promotes RNA stability, regulates translation and RNA localization, and mediates gene expression through its downstream effectors. Numerous studies have demonstrated that IGF2BP1 plays crucial roles in embryogenesis and carcinogenesis. IGF2BP1-modulated cell proliferation, invasion, and chemo-resistance in solid tumors have attracted researchers' attention. Additionally, several studies have highlighted the importance of IGF2BP1 in hematologic malignancies and hematological genetic diseases, positioning it as a promising therapeutic target for hematological disorders. However, there is a lack of systematic summaries regarding the IGF2BP1 gene within the hematological field. In this review, we provide a comprehensive overview of the discovery and molecular structure of IGF2BP1, along with recent studies on its role in regulating embryogenesis. We also focus on the mechanisms by which IGF2BP1 regulates hematological malignancies through its interactions with its targeted mRNAs. Furthermore, we systematically elucidate the function and mechanism of IGF2BP1 in promoting fetal hemoglobin expression in adult hematopoietic stem/progenitor cells. Finally, we discuss the limitations and challenges of IGF2BP1 as a therapeutic target, offering insights into its prospects.